Investigating the prevalence of diabetic peripheral neuropathy in patients diagnosed with type 2 diabetes mellitus - Dinesh Agarwal; Mayuri Sarma; Atul K Agarwal; Barkha Jain (Assam Journal of Internal Medicine)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder affecting millions of individuals reaching epidemic proportions globally. diabetic peripheral neuropathy (DPN) is one of the most prevalent and debilitating complications of T2DM, affecting the lower limbs and increasing the risk of foot ulcers, infections, and lower limb amputations. The current study aims to assess the prevalence and severity of DPN using monofilament and MNSI tests in patients diagnosed with T2DM and examine factors associated with the onset and progression of DPN. Objective: To study the prevalence of diabetic peripheral neuropathy in patients with type 2 diabetes mellitus. Materials and Methods: A cross-sectional study was conducted at the Department of Medicine & Diabetology, Marwari Hospital Assam. A total of 226 patients with type 2 diabetes were assessed for DPN using the Michigan Neuropathy Screening Instrument (MNSI). Results: The study assessed the prevalence of DPN among patients with diabetes mellitus. among the 226 participants, 32% had moderate neuropathy and 11% had severe neuropathy. Symptoms such as numbness, burning pain, and muscle cramps were reported by a significant proportion of participants. Examination findings showed foot-related complications and reduced nerve function in a considerable number of participants. The prevalence of neuropathy varied among different duration groups of patients with diabetes. The severity of neuropathy was higher among patients with longstanding diabetes. These findings emphasize the significant burden of DPN and the importance of diabetes management in managing and preventing diabetic neuropathy. Conclusion: This study revealed a considerable prevalence of DPN among patients with diabetes mellitus. The prevalence of neuropathy varied with the duration of diabetes, suggesting an increased risk with a longer disease duration. Timely intervention and appropriate diabetes management strategies are crucial in reducing the burden of DPN and improving patient outcomes.